Ag decorated SnO2 nanoparticles to enhance formaldehyde sensing properties. (January 2019) - Liu, Dan; Pan, Junli; Tang, Jianghong; Liu, Weiqiao; Bai, Shouli; Luo, Ruixian
Abstract: Silver, as a cheaper and good conductivity noble metal, has successfully been decorated on SnO2 nanoparticles to structure the Ag-SnO2 composites by a facile hydrothermal and in situ reduction method. The difference of structure and properties between SnO2 and composite was characterized by XRD, FESEM, elemental mapping, UV–vis spectroscopy, BET and XPS surface analysis. The sensing performance of SnO2 and composite to formaldehyde were also examined. The composite of 3.7 wt% Ag decorated SnO2 not only exhibits the high response to 10 ppm of formaldehyde but also has better stability and selectivity at an operating temperature of 125 °C. Moreover, the detection limit of the composite was determined to be 0.53 ppm, which is lower than that of pure SnO2 nanoparticles. The response mechanism of the composite to formaldehyde was also discussed in detail, which is attributed to the catalytic effect and the spillover effect of Ag nanoparticles. Graphical abstract: The response of the 3.7 wt% Ag-SnO2 composite exhibits response 7 times higher than pristine SnO2 to 10 ppm formaldehyde at 125 °C and good selectivity to other frequently encountered VOCs in indoor environments, and also has good stability, so, the composite is a promising material to detect trace harmful VOCs over other frequently encountered in indoor environments. Highlights: The response of Ag-SnO2 is 7 times higher than that of SnO2 to 10 ppm HCOH. The operating temperature of composite is reduced from 150 °C to 125 °C. The 3.8 wt% Ag decorated composite also has excellent selectivity and stability. Improving sensing properties is ascribed to the spillover and catalytic effects of Ag.